The Role of Local Communities in Planning and Management Walungan Cika-Cika Market as a Creative Tourism Destination - Qorina Zahra; Cika Putri Azahra (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Cika-Cika River Market is a community-based creative tourism destination developed through the initiative of local residents along the Cikapundung River in Bandung City. This destination emphasizes active community participation in tourism planning and management to achieve social, economic, and environmental sustainability. This study aims to analyze the role and level of local community participation, identify supporting and constraining factors, and formulate strategies to strengthen the community’s role in developing Cika-Cika River Market. The research employs a descriptive qualitative approach, with data collected through interviews, questionnaires, field observations, and literature review. Data analysis is conducted using SWOT analysis, supported by IFAS and EFAS matrices. The findings indicate that the local community plays a dominant role as the initiator and main manager of the destination, supported by strong social capital and a culture of mutual cooperation. However, challenges remain in terms of legal status, managerial capacity, and limited supporting facilities. Therefore, development strategies should focus on strengthening institutional capacity, improving MSME competencies, and enhancing community-based infrastructure to ensure the sustainability of the destination.